WHAT WILL THE FUTURE OF CREATIVITY AND INNOVATION IN PUBLIC RELATIONS LOOK LIKE? - Gurgu, Elena; Ilic, Milena; Rath, Sabyasachi; Gurgu, Ioana Andreea (Annals of Spiru Haret University. Economic Series, 2022)
Abstract: In this paper we talk about creativity in public relations, that is clear that we need. For us, creativity in public relations can be a mean, a novel way to accomplish an objective more easily, more efficiently and more quickly. It is clear that every client appreciates creativity, but in many situations it does not translate into events or visible messages for a mass audience and then it is not visible. We also talk in our paper about the profile of a creative relationalist, that must be: involved, informed, avid after work, possessing theoretical knowledge, having flexible and positive thinking, beeing visionary. In this paper we will try to demonstrate that creativity can occur in one of the following situations: either in strategy (positioning, planning), or in execution (tactics, presentation materials, information).